Institutional organization of regional management in Russia. - Partsvaniya, Vakhtang R.; Zarnadze, Albert A. (Bulletin of Geography. Socio-economic Series, 2007)
The consequences of the social and economic reforms of the 1990’s in Russia are analyzed. The advantages of forming and developing of complete economic systems are proven. The importance of the regional aspect in the functioning and development of the national economy is revealed. The theoretical and methodological basis of institutional organization of regional development in Russia is considered.